1999
DOI: 10.1002/(sici)1096-8628(19991029)86:5<420::aid-ajmg5>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Different molecular basis for spinal muscular atrophy in South African black patients

Abstract: Spinal muscular atrophy (SMA) is an autosomal recessive disorder occurring at a rate of between 1/5,000 and 1/10,000 births in most European countries. The phenotype results from the degeneration of the anterior horn cells of the spinal cord, resulting in symmetrical muscle weakness and wasting. The disorder can be classified according to the severity of the disease and the age of onset into three major types. Two candidate SMA genes, NAIP and SMN, isolated from the 5q13 region, have been reported to be homozy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 53 publications
1
26
2
1
Order By: Relevance
“…This may be one of the reasons for discrepancy in the deletion frequency in our patients group. The other reason for the difference in the frequency may be the population variation as in South African black patients 65 % [21] had deletion, Saudi Arabian patients had 72 % deletion [22], Polish had 63 % [23] and Vietnamese showed 41 % [24] deletion, while many other studies showed more than 90 % of deletion in SMN1 gene. We have observed that 2 of our type II patients and 1 of type III patient had deletion of exon 7 only but retaining exon 8 of SMN1 gene, this may be due to a gene conversion event at this locus.…”
Section: Discussionmentioning
confidence: 99%
“…This may be one of the reasons for discrepancy in the deletion frequency in our patients group. The other reason for the difference in the frequency may be the population variation as in South African black patients 65 % [21] had deletion, Saudi Arabian patients had 72 % deletion [22], Polish had 63 % [23] and Vietnamese showed 41 % [24] deletion, while many other studies showed more than 90 % of deletion in SMN1 gene. We have observed that 2 of our type II patients and 1 of type III patient had deletion of exon 7 only but retaining exon 8 of SMN1 gene, this may be due to a gene conversion event at this locus.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of small intragenic SMN1 mutations and/or of SMA unlinked to chromosome 5q13 may be higher in certain non-European populations, such as black South African patients [53], although data that do not support this hypothesis also exist [54].…”
Section: Smn1 Small Intragenic Mutationsmentioning
confidence: 93%
“…While no mutational variant was found in exons or splice-site consensus sequences, we cannot conclusively exclude a LIX1 expression defect in these or other non-SMN1 SMA patients until LIX1-expressing tissue can be interrogated. Furthermore, populations other than that represented by our predominantly Caucasian patient sample may have higher prevalence of SMA caused by mutations at other loci or undetected SMN1 mutations (Stevens et al 1999). …”
Section: Survey For Human Lix1 Mutationsmentioning
confidence: 96%